2010
DOI: 10.3945/jn.110.125799
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Parenteral Nutrition Induces Hepatic Inflammation, Steatosis, and Insulin Resistance in Neonatal Pigs1–3

Abstract: Prematurity and overfeeding in infants are associated with insulin resistance in childhood and may increase the risk of adult disease. Total parenteral nutrition (TPN) is a major source of infant nutritional support and may influence neonatal metabolic function. Our aim was to test the hypothesis that TPN induces increased adiposity and insulin resistance compared with enteral nutrition (EN) in neonatal pigs. Neonatal pigs were either fed enteral formula orally or i.v. administered a TPN mixture for 17 d; macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 57 publications
9
79
0
Order By: Relevance
“…The downstream metabolite of ceramide, sphingosine, did not show any difference in content in the liver either. It would therefore growth, which we reported previously (24). A major concern of PN-fed premature infants is the growth and neurodevelopment of the brain.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The downstream metabolite of ceramide, sphingosine, did not show any difference in content in the liver either. It would therefore growth, which we reported previously (24). A major concern of PN-fed premature infants is the growth and neurodevelopment of the brain.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, the presence of hepatomegaly in all PN groups occurred despite the prevention of steatosis and cholestasis in the OV and SL versus IL piglets (7). Our previous study also showed that TPN-induced hepatomegaly was due to increased protein and DNA, but not lipid content (24). The differential increase in these vital organs among all PN groups, but lower body growth rates in IL versus OV and SL piglets, points to a limitation in lean/skeletal muscle significantly (P < 0.05) decreased in all TPN groups compared with ENT.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although many components of TPN have been implicated in both animal and human studies of PNALD, recent interest has focused on the lipid component of TPN as being a major factor in the development of cholestasis (2). In the United States, only one form of lipid is fully approved for use in infants and children.…”
mentioning
confidence: 99%